Cold-Dependent Expression and Alternative Splicing of Arabidopsis Long Non-coding RNAs - Calixto, Cristiane P. G.; Tzioutziou, Nikoleta A.; James, Allan B.; Hornyik, Csaba; Guo, Wenbin; Zhang, Runxuan; Nimmo, Hugh G.; Brown, John W. S. (Frontiers in Plant Science, 2019)
Plants re-programme their gene expression when responding to changing environmental conditions. Besides differential gene expression, extensive alternative splicing (AS) of pre-mRNAs and changes in expression of long non-coding RNAs are associated with stress responses. RNA-sequencing of a diel time-series of the initial response of Arabidopsis thaliana rosettes to low temperature showed massive and rapid waves of both transcriptional and AS activity in protein-coding genes. We have now identified cold-dependent differential expression and differential alternative splicing of long non-coding RNAs (lncRNAs) including lncRNA pre-cursors of microRNAs (miRNAs) and trans-acting small-interfering RNAs (tasiRNAs). The high resolution of the time-series identified lncRNA genes which are regulated only at the level of AS, showed rapid cold-responsive changes in expression/AS. Detailed analyses suggest that the AS of some lncRNAs is highly sensitive to small temperature changes. The AtRTD2 transcriptome used in the RNA-seq analysis contained novel transcript isoform models for many lncRNAs. In particular, a splicing event in Tas1a which removed an intron that contained the miR173 processing and phased siRNAs generation sites was differentially alternatively spliced in response to cold. The cold-induced reduction of the spliced form of Tas1a and of the phased siRNAs suggests that splicing may enhance production of the siRNAs. Our results identify candidate lncRNAs that may contribute to the regulation of expression that determines the physiological processes essential for acclimation and freezing tolerance.